2017
DOI: 10.15626/eco-tech.2014.018
|View full text |Cite
|
Sign up to set email alerts
|

Metal speciation in soil at a contaminated glassworks site in southeastern Sweden

Abstract: Risk assessments of metal contaminated land are often based on total metal concentrations of the soil material, although it is well known that the potential for leaching is determined by the fractionation between labile metal forms and forms that are not to be assessed as geochemically active. In the present study, a 4-step sequential leaching procedure was applied to solid material from five subareas of a glass waste site in southeastern Sweden (including, for example, landfill areas and natural till material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Furthermore, the log K ow of BADGE·2HCl is 4.57, suggesting a high bioaccumulation potential of this compound. It has been reported that BADGE-based resins are used as protective coatings in paints used on boats and oil platforms . It was estimated that approximately 8.4% of epoxy resins consumed in 2004 globally were used in marine constructions …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the log K ow of BADGE·2HCl is 4.57, suggesting a high bioaccumulation potential of this compound. It has been reported that BADGE-based resins are used as protective coatings in paints used on boats and oil platforms . It was estimated that approximately 8.4% of epoxy resins consumed in 2004 globally were used in marine constructions …”
Section: Resultsmentioning
confidence: 99%